The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7196/ajhpe.436
|View full text |Cite
|
Sign up to set email alerts
|

Field trips as an intervention to enhance pharmacy students’ positive perception of a management module in their final year: A pilot study

Abstract: Background. Management training is an important aspect of pharmacy training, as many pharmacists are appointed in management positions early in their careers. However, students struggle to see the importance and relevance of a management module in the final year of the BPharm curriculum and show low levels of motivation and engagement with regard to the module. A possible strategy to change students' perceptions of the importance of a management module is the inclusion of field trips in the curriculum. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Based on Table 8 regarding descriptive statistics of students' response to cricket batting skill gauge, it was found that 1 student had a very good response level, 12 students had a good response level and 17 students had enough response level. Positive and negative responses of students are a common phenomenon in universities (Eksteen & Reitsma, 2015). Positive responses cause students to feel satisfied with the learning used, especially in the use of media, because it is important to understand student responses in order to know about their way of thinking (Hasan & Bao, 2020;Kamid et al, 2021;Rajabalee & Santally, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on Table 8 regarding descriptive statistics of students' response to cricket batting skill gauge, it was found that 1 student had a very good response level, 12 students had a good response level and 17 students had enough response level. Positive and negative responses of students are a common phenomenon in universities (Eksteen & Reitsma, 2015). Positive responses cause students to feel satisfied with the learning used, especially in the use of media, because it is important to understand student responses in order to know about their way of thinking (Hasan & Bao, 2020;Kamid et al, 2021;Rajabalee & Santally, 2021).…”
Section: Discussionmentioning
confidence: 99%